SISTEM INFORMASI AKUNTANSI UNTUK USAHA MIKRO, KECIL DAN MENENGAH (UMKM) : PENGHAMBAT ATAU SOLUSI? (Studi Kasus Usaha Kecil dan Menengah di Kabupaten Jember) - Mustofa, Ahmad; Setyawan, Bimo; Azaro, Khoirin; Khoirunisa, Rizqi; Kurnia, Lely Indah (Media Mahardhika, 2025)
Indonesia's economic structure is dominated by Micro, Small, and Medium Enterprises (MSMEs), which play a strategic role in economic growth and poverty alleviation. The implementation of accounting information systems in MSMEs is a crucial issue in improving financial management efficiency and transparency. This study aims to explore the challenges and successes of implementing accounting information systems in MSMEs in Jember Regency. The research method used is qualitative with an exploratory approach. Data were collected through interviews and observations on three types of MSMEs: service, trade, and manufacturing. The results show that business scale, management support, and the level of education and training influence the successful implementation of accounting information systems. MSME actors generally recognize the benefits of digitalization in financial record-keeping, but there is a gap in understanding applicable accounting standards. Other factors, such as limited human resources and perceptions of system complexity, also pose challenges in the adoption of accounting information systems. This study recommends enhancing education and training programs for MSME actors to improve their understanding and adoption of optimal accounting systems.